Interhypothalamic Adhesion in a 9-Month-Old Male with Cleft Palate - Matthew T. Whitehead; Jacqueline D. S. Angel (Case Reports in Radiology)
A 9-month-old male infant with multiple congenital anomalies including cleft lip and palate was referred to us for a brain MR to exclude additional intracranial abnormalities. Imaging revealed an interhypothalamic adhesion, which we present as a possible forme fruste of holoprosencephaly.